Highly Photoconductive InP Quantum Dots Films and Solar Cells - Crisp, Ryan; Kirkwood, Nicholas; Grimaldi, Gianluca; Kinge, Sachin; Siebbeles, Laurens D. A.; Houtepen, Arjan J. (ACS Applied Energy Materials, 2018)
InP and InZnP colloidal quantum dots (QDs) are promising materials for application in light-emitting devices, transistors, photovoltaics, and photocatalytic cells. In addition to possessing an appropriate bandgap, high absorption coefficient, and high bulk carrier mobilities, the intrinsic toxicity of InP and InZnP is much lower than for competing QDs that contain Cd or Pb providing a potentially safer commercial product. However, compared to other colloidal QDs, InP QDs remain sparsely used in devices and their electronic transport properties are largely unexplored. Here, we use time-resolved microwave conductivity measurements to study charge transport in films of InP and InZnP colloidal quantum dots capped with a variety of short ligands. We find that transport in InP QDs is dominated by trapping effects, which are mitigated in InZnP QDs. We improve charge carrier mobilities with a range of ligand-exchange treatments and for the best treatments reach mobilities and lifetimes on par with those of PbS QD films used in efficient solar cells. To demonstrate the device-grade quality of these films, we construct solar cells based on InP & InZnP QDs with power conversion efficiencies of 0.65 and 1.2%, respectively. This represents a large step forward in developing Cd- and Pb-free next-generation optoelectronic devices.
Keywords: indium phosphide; nanocrystals; quantum dots; photovoltaic; time-resolved microwave conductivity; ligand-exchange